Comparison of the laryngeal view during intubation using Airtraq and Macintosh laryngoscopes in patients with cervical spine immobilization and mouth opening limitation - Jae-Chul Koh (Korean Journal of Anesthesiology, 2010)
BackgroundFor patients suspicious of cervical spine injury, a Philadelphia cervical collar is usually applied. Application of Philadelphia cervical collar may cause difficult airway. The aim of this study was to evaluate the laryngeal view and the success rate at first intubation attempt of the Airtraq and conventional laryngoscopy in patients with simulated cervical spine injury after application of a Philadelphia cervical collar.MethodsAnesthesia was induced with propofol, remifentanil, and rocuronium. After a Philadelphia cervical collar applied, patients were randomly assigned to tracheal intubation with an Airtraq (Group A, n = 25) or with conventional laryngoscopy (Group L, n = 25). Measurements included intubation time, success rate of first intubation attempt, number of intubation attempts, and percentage of glottic opening (POGO) score. Mean blood pressure and heart rate were also recorded at baseline, just before and after intubation.ResultsThe success rate of the first attempt in Group A (96%) was significantly greater than with the Group L (40%). POGO score was significantly greater in Group A (84 ± 20%) than in Group L (6 ± 11%). The duration of successful intubation at first tracheal intubation attempt and hemodynamic changes were not significantly different between the two groups.ConclusionsThe Airtraq offers a better laryngeal view and higher success rate at first intubation attempt in patients who are applied with a Philadelphia cervical collar due to suspicion of cervical spine injury.